Deregulation of Regulatory T Cells in Acute-on-Chronic Liver Failure: A Rat Model. (15th January 2017) - Ni, Shunlan; Li, Shanshan; Yang, Naibin; Tang, Xinyue; Zhang, Shengguo; Hu, Danping; Lu, Mingqin
Abstract : Aims . Acute-on-chronic liver failure (ACLF) and acute liver failure (ALF) are similar in many respects during their acute exacerbation; however, ACLF generally has a poorer prognosis. We aimed to investigate the role and dynamic changes of regulatory T cell (Treg) and T helper 17 (Th17) cell proportions during ACLF progress. Methods . All rats were classified into two groups randomly: ACLF group and ALF group (control group). The rat model of ACLF was preestablished by intraperitoneal injection of carbon tetrachloride for 2 months. Then acute liver injury was induced by combined D-galactosamine and lipopolysaccharide. Six time points were examined before or after acute induction. Liver samples were performed with hematoxylin-eosin and Masson staining; circulatory Treg and Th17 cell frequencies were determined using flow cytometry assays; serum levels of alanine aminotransferase, aspartate aminotransferase, interleukin-10 (IL-10), and interferon- γ (IFN- γ ) were examined. Results . In group ACLF, both Th17 cell proportion and IFN- γ level presented upgrade firstly and then descend latter tendency; the trends of Treg cell proportion and IL-10 level were observed to gradually decrease and became stable. Conclusion . The Treg cells played an important role in the immunologic mechanism during the process of ACLF. And the function of Treg cells in ACLF was defective.